2021
DOI: 10.1038/s41598-021-88796-2
|View full text |Cite
|
Sign up to set email alerts
|

Computational design of single-stranded DNA hairpin aptamers immobilized on a biosensor substrate

Abstract: Aptamer interactions with a surface of attachment are central to the design and performance of aptamer-based biosensors. We have developed a computational modeling approach to study different system designs—including different aptamer-attachment ends, aptamer surface densities, aptamer orientations, and solvent solutions—and applied it to an anti MUC1 aptamer tethered to a silica biosensor substrate. Amongst all the system designs explored, we found that attaching the anti MUC1 aptamer through the 5′ terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This not only impacts their conformation but also enhances the comprehension of DNA-aptamer interactions with the PDA surface. However, previous experimental and computational studies have demonstrated that the orientation or conformation of a tethered biorecognition element on a biosensor surface can alter upon immobilization, significantly affecting the biosensor’s performance ( Wong and Pettitt, 2004 ; Jeddi and Saiz, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…This not only impacts their conformation but also enhances the comprehension of DNA-aptamer interactions with the PDA surface. However, previous experimental and computational studies have demonstrated that the orientation or conformation of a tethered biorecognition element on a biosensor surface can alter upon immobilization, significantly affecting the biosensor’s performance ( Wong and Pettitt, 2004 ; Jeddi and Saiz, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides the choice of the chemical conjugation route, aptamer immobilization should also be tailored in terms of the surface coverage density and orientation to achieve the proper functional folding of the aptamers [ 100 , 101 , 102 ]. Proper aptamer density on a surface is crucial for achieving sufficient binding sites for the target, while minimizing steric hindrance and electrostatic repulsion between neighboring aptamers.…”
Section: Aptasensorsmentioning
confidence: 99%